PENERAPAN METODE PICTURE AND PICTURE DALAM PEMBELAJARAN MENULIS TEKS EKSPOSISI PADA SISWA KELAS X SMK - Yulyani, Yulyani; Mustika, R Ika (IKIP Siliwangi, 2019)
This research is motivated by the existence of observational data that shows the value of student learning outcomes is low, so students experience difficulties during learning. Based on this, the study of exposition text writing is carried out using the picture and picture method. The objectives to be obtained are to find out the application of the picture and picture method in improving students' writing skills and to find out the differences in the learning outcomes of writing exposition text using picture and picture. The research method used is Quasi-Experimental Design. The sample used in the study was the X class of Vocational School which numbered 25 students. Data collection techniques with initial test data collection and final test data as a comparison. Based on the results of these tests, then there are results of the average pretest value obtained value of 63.20 and the results of the average posttest value obtained value of 81.80 so that the difference in value with a difference of 18.6. This shows that the application of the picture and picture method is effectively used so that it can improve the ability to write exposition text in class X of Vocational School.